2015
DOI: 10.1371/journal.pone.0116715
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Immunochromatography for Rapid and Sensitive Typing of Seasonal Influenza Viruses

Abstract: Lateral flow tests also known as Immunochromatography (IC) is an antigen-detection method conducted on a nitrocellulose membrane that can be completed in less than 20 min. IC has been used as an important rapid test for clinical diagnosis and surveillance of influenza viruses, but the IC sensitivity is relatively low (approximately 60%) and the limit of detection (LOD) is as low as 10³ pfu per reaction. Recently, we reported an improved IC assay using antibodies conjugated with fluorescent beads (fluorescent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…However, in our study, the sensitivity of LFA to detect influenza viruses A and B was not significantly different. Further analysis found that in one of the included literatures, LFA was more sensitive in detecting influenza virus B than influenza virus A in nasal swabs [ 29 ]. Therefore, we infer that collecting nasal swab samples may enhance the sensitivity of detecting influenza virus B.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the sensitivity of LFA to detect influenza viruses A and B was not significantly different. Further analysis found that in one of the included literatures, LFA was more sensitive in detecting influenza virus B than influenza virus A in nasal swabs [ 29 ]. Therefore, we infer that collecting nasal swab samples may enhance the sensitivity of detecting influenza virus B.…”
Section: Discussionmentioning
confidence: 99%
“…The reported performance of conventional immunoassay RDTs was about 7 × 10 4 - 7 × 10 5 PFU/mL for H5N3 34 , 35 . Recently, various approaches have been applied to improve the rapid diagnostic systems for accurate and quick analysis with different influenza subtype viruses; A fluorescent immunochromatographic test for seasonal influenza viruses has been reported to detect H5N1 virus at 83.7 PFU/reaction, but the clinical study was performed only with Influenza A type, not H5N1 36 . Although recent developments in rapid diagnostic tests employ nanomaterials, including nanoparticles 37 and graphene films 38 , to detect influenza H5 recombinant antigen, such methods still need further improvements and verification in clinical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Given the demand for multiplex testing and the major advantages of the lateral flow assay over alternative rapid diagnostic platforms, this study aimed to adapt the simplicity of the membrane-based lateral flow assay and multiplex techniques. Various fluorescent materials have been applied for lateral flow assays as alternative to conventional gold nanoparticles to detect influenza A as POCT [11][12][13][14][15][16]. Also, self-contained and disposable diagnostic devices have been developed [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%